Country image and consumer evaluation of imported products: test of a hierarchical model in four countries. (24th September 2020) - Thøgersen, John; Aschemann-Witzel, Jessica; Pedersen, Susanne
Abstract : Purpose: This paper aims to test the general validity of a hierarchical model of country image conceptualizations across countries that differ in socio-economic development and distance to the exporting country. Design/methodology/approach: Representative consumer samples in Germany, France, China and Thailand ( N ∼ 1, 000 per country) completed an online survey on three levels of country image regarding Denmark and attitudes towards buying an organic food product from Denmark. Data were analyzed using confirmatory factor analysis and structural equation modelling. Findings: The hierarchical country image model fitted the data well in the two European countries, but not in the two Asian countries. It appears that the hierarchical relationships proposed by the model require a high level of familiarity with and knowledge of the origin country and the product type. Research limitations/implications: The application scope of the model is considerably narrower than implied by earlier research. Further research should combine data from a number of sources to investigate the model's application further. Practical implications: Exporters must pay attention to both the general image of their country and the image of their country with regard to their specific product category, as this impacts consumer product evaluations. Originality/value: International trade and the success of export strategies ultimately depend on consumer acceptance in importing countries. This study demonstrates how consumer perception of imported products is affected by the exporting country's image, which may be more or less elaborate and differentiated. It gives exporters new insight into how they can make their marketing effective when entering markets.